2016
DOI: 10.1080/0886022x.2016.1256321
|View full text |Cite
|
Sign up to set email alerts
|

Dietary zinc modifies diabetic-induced renal pathology in rats

Abstract: This study was conducted to investigate how far dietary zinc (Zn) modifies the histomorphological alterations induced by diabetes in rat kidneys. The animals were divided into negative control group (10 rats). Diabetes was induced in thirty animals by streptozotocin. After confirming diabetes, the animals were divided into three groups (n = 10). Group II served as the positive control group (fed on standard diet), group III was fed on Zn deficient diet, and group IV was fed on Zn supplemented diet. Caspase-3 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 73 publications
1
7
0
1
Order By: Relevance
“…In the present study, glomerulonephritis was discovered in the clozapine group; similar findings were obtained in other studies, with several psychotropic drugs (e.g., ziprasidone, olanzapine, chlorpromazine, and aripiprazole) found to injure the kidneys and cause their dysfunction (through, for example, CKD, interstitial nephritis, and glomerulonephritis) [76,77]. Renal function is commonly evaluated using serum creatinine and BUN levels [78], and in patients with moderate-severe CKD, disease progression was associated with higher creatinine and BUN levels [79].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, glomerulonephritis was discovered in the clozapine group; similar findings were obtained in other studies, with several psychotropic drugs (e.g., ziprasidone, olanzapine, chlorpromazine, and aripiprazole) found to injure the kidneys and cause their dysfunction (through, for example, CKD, interstitial nephritis, and glomerulonephritis) [76,77]. Renal function is commonly evaluated using serum creatinine and BUN levels [78], and in patients with moderate-severe CKD, disease progression was associated with higher creatinine and BUN levels [79].…”
Section: Discussionsupporting
confidence: 91%
“…Firneisz [39] showed that NAFLD is closely related to and is the leading cause of chronic liver disease predicted by T2D, which has been shown to cause disruption in endoplasmic reticulum homeostasis (ER stress), which leads to mitochondrial dysfunction, oxidative stress, inflammation and cell death [40]. Researchers have also shown morphological complications in the kidney characterized by widening of Bowman's spaces and thickening of basement membrane in the renal cortices and loss of apical microvilli with swollen mitochondria in the proximal convoluted tubules of streptozotocin-induced diabetic rats [41]. Our ultrastructural studies confirmed damage to the cell and organelles, including shrunken nucleus, vacuolated cytoplasm, fragmented rough endoplasmic reticulum (ER) and swelling and disintegration of mitochondria (as seen by the decrease in mitochondrial number and area) in the liver of GK rats.…”
Section: Discussionmentioning
confidence: 99%
“…The other half of the kidney was cut into 1 mm 2 pieces and were immediately dipped in 2.5% glutaraldehyde and kept in the refrigerator at 4 °C for 2 h and processed for examination with PEM-100 transmission electron microscope [48] at EM unit in Mansoura University.…”
Section: Methodsmentioning
confidence: 99%